Factors affecting the pharmaceutical waste management practices of independent community pharmacists in Manila City - Fernandez, Leila Avior R.; Gaspar, Reinier B; Mercado, Jemina Mar C; Robles, Yolanda (Manila College of Pharmacy, University of the Philippines Manila, 2025)
Pharmaceutical waste management (PWM) in community pharmacies is a growing concern, as improper disposal of medicines can harm both public health and the environment. In the Philippines, independent community pharmacies often lack clear, pharmacy-specific guidelines on waste management, and research on their practices and influencing factors remains limited.
This study aimed to determine the factors influencing PWM practices among independent community pharmacists in Manila City.

A mixed-methods approach was employed, combining a cross-sectional survey of independent community pharmacists and key informant interviews. The quantitative component assessed sociodemographic characteristics, training experiences, awareness of national standards, and PWM practices using a structured questionnaire based on the 2022 Health Care Waste Management Manual by the Department of Health. The qualitative component explored pharmacists’ perspectives and barriers through semi-structured interviews. Descriptive statistics, correlation, and regression analyses were used for quantitative data, while thematic analysis was applied to qualitative transcripts.

Most respondents were young, female, and held bachelor’s degrees, with moderate experience in community pharmacy. Only about half reported receiving PWM training, and awareness of national standards was limited. Waste minimization strategies were commonly practiced, but safe segregation and disposal were inconsistent, with many pharmacists relying on general waste streams. No significant relationships were found between sociodemographic characteristics, training, or awareness and proper PWM practices. Qualitative findings highlighted that pharmacists recognized the importance of PWM but faced barriers, including a lack of clear guidelines, limited infrastructure, and insufficient system-level support.

The study reveals that improving PWM in community pharmacies requires more than individual knowledge or training. Systemic interventions, including the development of pharmacy-specific guidelines, better disposal infrastructure, and integration of PWM into pharmacy education and regulatory requirements, are needed to support safe and effective waste management practices in this setting.
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, July 2025
Keywords: Pharmaceutical waste -- Disposal practices -- Community pharmacies -- Philippines